Towards socially responsible corporate governance with authorities’ interventions - Andreja Primec; Jernej Belak (Management : Journal of Contemporary Management Issues, 2018)
Due to the fact that moral commitments of individuals as well as of corporations were not enough for successful fostering of the socially responsible behaviour of corporations, we are facing the new international and national laws fostering the reporting on non-financial activities of the corporations. We can, therefore, observe how the development of theory on corporate governance, in a relationship with the corporate social responsibility has finally resulted in significant changes in international as well as national legislatives. Therefore, in our paper we examine the legal framework of the EU on corporate social responsibility reporting as well as on non-financial statements of corporations. We analyse the aim, the content and the legal effects of this statements under the last amendments from 2014 (Directive 2014/95/EU) and evaluate its contribution to fortifying the role of corporate social responsibility in the corporate governance of EU corporations. The presented paper argues the importance of institutional development in the context of corporate governance and the influence of institutional measures on corporate ethical behaviour and, consequently, on their success implementing the simple aim to protect the interests of all corporations’ stakeholders within the framework of corporate functioning.